Australian Charter of Employment Rights - Bromberg, Mordy; Irving, Mark, 1967- (Victoria, Australia : Australian Institute of Employment Rights : Hardie Grant Books, 2007)
"The Australian Charter of Employment Rights is a blueprint for the future of industrial relations in Australia." "The Charter is a back-to-basics attempt to define the rights of workers and employers. It is a simply expressed contemporary document that draws upon international as well as uniquely Australian rights and values to create a set of rights and obligations which all workplaces are encouraged to adopt and observe. The Charter enables a critique of current labour laws and any proposals for change." "The Australian Charter of Employment Rights is the collaborative effort of seventeen of Australia's leading IR practitioners, lawyers and economists, edited by Mordy Bromberg and Mark Irving."--BOOK JACKET.
1. Good Faith Performance -- 2. Work with Dignity -- 3. Freedom from Discrimination and Harassment -- 4. A Safe and Healthy Workplace -- 5. Workplace Democracy -- 6. Union Membership and Representation -- 7. Protection from Unfair Dismissal -- 8. Fair Minimum Standards -- 9. Fairness and Balance in Industrial Bargaining -- 10. Effective Dispute Resolution -- 11. The Scope of the Charter -- 12. Economic Perspectives on Workers' Rights -- 13. The Right to Work.
Includes index.
Keywords: Labor laws and legislation -- Australia; Employee rights -- Australia; Industrial relations -- Australia